Analisis Pembelajaran Berdiferensiasi dalam Kurikulum Merdeka di Sekolah Dasar - Soviyani, Soviyani; Barokah, Ihda Lailatul; Putri, Rahmanisa Daiyah; Wahyudi, Apri (Tunas Nusantara, 2024)
Every student in the class has their own uniqueness. They come from diverse backgrounds, with different learning preferences, interests and paces of learning. Their readiness to receive the material also varies. This research is important to disseminate widely because it is hoped that it can provide insight into the concepts, characteristics, principles and implementation of differentiated learning in the independent curriculum at the elementary school level. This study uses a qualitative approach with a literature review method chosen to analyze various concepts, theories and previous research findings related to differentiated learning and its application at the elementary school level.